2023
DOI: 10.1021/acssuschemeng.2c06514
|View full text |Cite
|
Sign up to set email alerts
|

Circular Economy Electrochemistry: Creating Additive Manufacturing Feedstocks for Caffeine Detection from Post-Industrial Coffee Pod Waste

Abstract: The recycling of post-industrial waste poly(lactic acid) (PI-PLA) from coffee machine pods into electroanalytical sensors for the detection of caffeine in real tea and coffee samples is reported herein. The PI-PLA is transformed into both nonconductive and conductive filaments to produce full electroanalytical cells, including additively manufactured electrodes (AMEs). The electroanalytical cell was designed utilizing separate prints for the cell body and electrodes to increase the recyclability of the system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 50 publications
3
36
0
Order By: Relevance
“…In rPLA, there are equal amounts of the three carbon environments, leading to an XPS C 1s fitting of three peaks with similar intensities. 8 In castor oil, there is significantly more C–C/C–H bonding than C–OH and O–CO bonding, leading to a peak of much higher intensity, significantly more than that seen in Fig. 2A.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…In rPLA, there are equal amounts of the three carbon environments, leading to an XPS C 1s fitting of three peaks with similar intensities. 8 In castor oil, there is significantly more C–C/C–H bonding than C–OH and O–CO bonding, leading to a peak of much higher intensity, significantly more than that seen in Fig. 2A.…”
Section: Resultsmentioning
confidence: 81%
“…5 This perfect circular economy remains hypothetical for the time being, but research around the concept is gaining traction, with more work transitioning from a reliance on virgin materials, particularly non-renewable sources. 6,7 Recently, the idea of circular economy in electrochemistry was introduced, 8 focussing on using additive manufacturing within electrochemistry to produce electroanalytical sensing platforms. The use of additive manufacturing within electrochemistry has seen a sharp increase in the last decade due to its many benefits, such as low cost of equipment and consumables, rapid prototyping capabilities, the ability to explore complex electrode geometries without high manufacturing costs, 9,10 and low waste production, amongst other benefits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the rAME shows an increased electrochemical surface area of 0.081 ± 0.001 cm 2 compared to 0.075 ± 0.001 and 0.074 ± 0.002 cm 2 . This increase in electrochemical area is in agreement with the XPS and SEM data obtained earlier, whereby an increased amount of graphitic carbon was seen on the surface of non-activated rAMEs compared to standard commercial ones, as seen in other studies. , This data shows that the recycled conductive filament gives excellent electrochemical performance compared to the commercial equivalent.…”
Section: Resultsmentioning
confidence: 99%
“…Outstanding papers in the literature revealed that the polymeric materials can be reusable by numerous ways, (i) recycling carbon fibers and using them as additive option in the fused filament fabrication (FFF) process of PLA, (ii) reusing glass fiber obtained from turbine blades to reinforce the mechanical properties of PLA material, (iii) recycling PET and polypropylene aim for manufacturing additive filaments with similar mechanical proprieties to the commercial filament and, (iv) combining waste of PLA recovered from coffee pods with native poly­(ethylene glycol) and carbon black particles aim for manufacturing a suitable option of conductive additive filament that can be dedicate to constructed electrodes. , However, to the best of our knowledge, the aforementioned studies do not explore residues of thermoplastic as binder structures for manufacturing disposable electrochemical sensors, which are of high potential in the modern analytical chemistry field, including forensic, , pharmaceutical, environmental, , food and biological ones. …”
Section: Introductionmentioning
confidence: 99%